Perlindungan Hukum Hak Ganti Rugi Pekerja PKWT Akibat PHK Sepihak: Studi Putusan Mahkamah Agung Nomor 560 K/Pdt.Sus Phi/2023 - Raka Fachri Maulia Kamal; Muhamad Abas; Yuniar Rahmatiar (Jurnal Hukum Lex Generalis, 2026)
This study examines Supreme Court Decision No. 560 K/Pdt.Sus-PHI/2023 regarding the arbitrary dismissal of a fixed-term contract (PKWT) worker due to COVID-19. Using normative judicial methods, it highlights violations of human rights and legal protection. Findings show that under Article 62 of the Labor Law, employers must pay the remaining contract wages for early termination. The Supreme Court granted the worker’s appeal, citing the lower court's legal errors. Consequently, the company was ordered to pay IDR 33,400,000 in compensation to ensure substantive justice and protect the worker’s normative rights.